Does Sharia Support Cloning? A Qualitative Analysis - Hasan, Sabbir (International Journal of Islamic Khazanah, 2023)
Recent developments in genetics and biotechnology have ushered in a new era of health advancement. Islam is the name of a faith that inspires its followers to innovate within the limits of Islamic law in the pursuit of knowledge and to improve the quality of life. Modern biotechnology, especially animal cloning, has helped advance human civilisation's social, economic, and health aspects. Therapeutic cloning has uncovered enormous possibilities in medical practice. However, cloning technology is also believed to have the potential for reproductive cloning, which raises ethical issues. Islamic countries need to reach a consensus on this important issue. The need for a Sharia perspective to improve science and technology is evident in the context of greater health development. Muslim scholars need to immediately take a logical and much-needed step towards stem cell and cloning research that considers the scientific benefits and ethical, legal, and Sharia implications. The present study aims to evaluate the different views of Muslim jurists on therapeutic and reproductive cloning by clarifying the Shariah position on this controversial issue.